CEREBRAL VENOUS SINUS THROMBOSIS WITH GOOD RESPONSE TO HEPARINIZATION THERAPY: TWO CASE REPORT AND DIAGNOSTIC ALGORITHM - Indah, Carolin Tiara Lestari; Tini, Kumara; Susilawathi, Ni Made; Wijayanti, Ida Ayu Sri; Mahadewi, Ni Putu Ayu Putri; Pramaswari, Anak Ayu Agung; Mahaalit Aribawa, I Gusti Ngurah; Dewi, Putu Utami; Krisnawardhani Kumbara, Cokorda Istri Yuliandari (MNJ (Malang Neurology Journal), 2024)
Cerebral venous sinus thrombosis (CVST) is an uncommon condition of cerebral venous sinus thrombosis with a varied clinical presentation that can be diagnostically challenging. Intravenous heparin is the optimal immediate anticoagulant according to the European Academy of Neurology (EAN) guideline 2017. This report aims to describe highly suspicious CVST clinical features and suggest a diagnostic algorithm based on two cases of CVST found in our center. The first case is a 52-year-old man who presented with serial seizures preceded by subacute headache and diparesis. Non-contrast head CT (NCCT) showed multifocal haemorrhages and cord signs. The second case is a 19-year-old woman who presented with slowly decreased consciousness, headache, and a history of upper respiratory infection. Diffuse cerebral edema was revealed in NCCT. Both of these patients had thrombosis in superior sagittal sinus, right transverse, and sigmoid sinus. Heparinization was conducted and continued with rivaroxaban with a good response. CVST is rare case and often unrecognized; since it has serious complications, early diagnosis and treatment improve prognosis and survival.